Towards a comprehensive research design for studying integrated care. (September 2014) - Dessers, Ezra; Vrijhoef, Hubertus JM; Annemans, Lieven; Cambré, Bart; Dhondt, Steven; Hellings, Johan; Hermans, Koen; Kenis, Patrick; Nys, Herman; Vandijck, Dominique; Van Hootegem, Geert
Given that integrated care includes many different aspects, this paper seeks to design a comprehensive research approach and explains how this approach is applied in the CORTEXS research project on integrated care in the Flemish Community in Belgium. A systemic view on integrated care is translated into a multi-level, multi-disciplinary, multi-method and multi-stakeholder research design. A phased approach of taxonomy development and literature review, comparative case studies, social lab activities and valorisation initiatives is devised in order to link fundamental research with strategic valorisation of the research results. While this innovative comprehensiveness is seen as a major strength, it is acknowledged that the research design comes with certain risks that need to be tackled.